Visualising migration flow data with circular plots - Nikola Sander; Guy J. Abel; Ramon Bauer; Johannes Schmidt (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2014)
Effective visualisations of migration flows can substantially enhance our understanding of underlying patterns and trends. However, commonly used migration maps that show place-to-place flows as stroked lines drawn atop a geographic map fall short of conveying the complexities of human movement in a clear and compelling manner. We introduce circular migration plots, a new method for visualising and exploring migration flow tables in an intuitively graspable way. Our approach aims to provide detailed quantitative information on the intensities and patterns of migration flows around the globe by using a visualization design that is effective and visually appealing. The key elements of the design are (a) the arrangement of origins and destinations of migration flows in a circular layout, (b) the scaling of individual flows to allow the entire system to be shown simultaneously, (c) the expression of the volume of movement through the width of the flow and its direction through the colour of the origin. Drawing on new estimates of 5-year bilateral migration flows between 196 countries, we demonstrate how to create circular migration plots at regional and country levels using three alternative software packages: Circos, R, and the JavaScript library d3.js. Circular migration plots considerably improve our ability to graphically evaluate complex patterns and trends in migration flow data, and for communicating migration research to scientists in other disciplines and to the general public. Our visualisation method is applicable to other kinds of flow data, including trade and remittances flows.
Keywords: 300; Migration; flow data; visualisation; D3